The Government's Role in Public Services regarding Information Disclosure on Electronic KTP Recording at the Medan Baru District Office - Lubis, Fachrizaly; Jamillah, Jamillah; Syaputra, Muhammad Yusrizal Adi (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
Public services are services provided by the government as state administrators to the community, Electronic KTP is a population document containing a security / control system from both the administrative and information technology side based on the national population database. The type of research used is normative juridical and the nature of the research used is descriptive analytical. The data collection technique used 2 (two) methods, namely library research and field research. Data analysis was carried out qualitatively. The results of research in 2011 the population of Medan Baru Subdistrict is estimated to have reached 57,962 people, the management of KTP is recorded and documented in a special agenda book of Electronic KTP, it is absolutely necessary to have valid population data and already have a NIK and photo recording, signature, fingerprint, and population iris, the results of the discussion of Law Number 24 of 2013 in Article 1 number 21 concerning the population administration information system, the government provides data verification services, photo recording, signatures, fingerprints and iris of the population at the Electronic KTP service place, lack of blanks from central government, lack of clear information for the public and limited Electronic KTP security tools, in conclusion, Electronic KTP contains a security code and electronic records as a means of verification and validation of a person's identity data.